Abordagem do conteúdo "ondas" no ensino médio na perspectiva CTS estruturada a partir dos tês momentos pedagógicos. - Pieri, Helena da Gloria (2017)
Among the difficulties found on teaching and learning physics, certainly, didactic strategies occupy a prominent position. They may act in a way which seeks to bring the content under discussion closer to the needs and desires of the students, proving to be conducive to learning. In this context, the present dissertation, which is part of the research line "Theoreticalmethodological foundations for the teaching of Science and Mathematics", elected Paulo Freire's conception was chosen as a pedagogical bias. Based on this, it was based on other theoretical perspectives derived from the author's studies, such as the science-technology society approach (CTS) and the three pedagogical moments (DELIZOICOV; ANGOTTI, 1991). The choice was based on the intention of proposing strategies which promote, among other things, the training of citizens who are scientifically literate and who can act critically and consciously in society. As a result, a didactic sequence was developed for the "waves" content in high school, supported by the three pedagogical moments and the CTS perspective, evaluating its relevance in terms of didactic strategy and contemplation of educational objectives. The questioning guiding the study was thus defined: to what extent does the CTS approach favor the establishment of relations between scientific knowledge and living situations? Does this approach, structured on the basis of the three pedagogical moments, contribute to reflect the implications that science has on the social, cultural and historical life of young people? The didactic sequence was structured in eighteen meetings and developed in a state public school in the city of Passo Fundo, RS. The qualitative and participatory research focused on the analysis of the eighteen meetings, with emphasis on the evaluation of two central aspects: the didactic strategy and the contemplation of the educational objectives established for the content. In the first case, the logbooks prepared by the teacher / researcher were taken as an instrument for collecting data; And in the second case, the plot of a play developed at the last meeting was analyzed as a form of systematization of the content addressed. As results, which are expressed in the categories and subcategories extracted from the data, the study pointed to the feasibility of the proposal and the importance of proposing teaching activities guided bythe approximation of the contents with the experiential situations, particularly those that provide the training for citizenship. In addition, the study elucidated the relevance of proposing debates and the insertion of controversial themes to instigate the critical thinking of the students and potentially significant for the appropriation of the concepts in Physics. Finally, it is emphasized that this dissertation is accompanied by an educational product that brings together the material used in the meetings and the didactic sequence developed. This product is available in a bolt.